The impact of climate change on the Palestinian sectoral reallocation of labor - Sameh Hallaq; Yousuf Daas (Levy Economics Institute of Bard College, 2023)
The research leverages yearly variations in climate variables, such as rainfall and temperature, across the West Bank from 1999 to 2018 to assess their influence on individuals' decisions to stay in the agricultural sector. The main findings suggest that an increase in rainfall in the previous year is associated with a higher proportion of workers in the agricultural sector, especially in regions where agriculture is the primary economic activity. Temperature variation is also an important factor. An increase in the maximum temperature will generally have a negative effect on the supply of labor in the agricultural sector, while an increase in the minimum temperature may have a positive effect. However, this effect varies across different regions of the West Bank, reflecting the diverse agricultural practices and irrigation methods employed. The study also examines two potential mechanisms through which climate change affects labor decisions: agricultural labor migration to the Israeli labor market and how climate shocks affect agricultural wages.
Keywords: J01; J43; Q54; 330; Labor Supply; Climate Change; Agriculture; West Bank